FoodConnect: um software de gestão logística para auxiliar no combate à fome e redução de desperdícios - Ferreira, Maykon Willyam de Sousa; Veras, Maria Mislene Rosado de Sousa; Anchiêta, Rafael Torres (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia); 2025: Anais Estendidos do XXXI Simpósio Brasileiro de Sistemas Multimídia e WebDO - 10.5753/webmedia_estendido.2025.16400, 2025)
Addressing the paradox between the high volume of discarded food and the number of people facing hunger, FoodConnect offers a technological solution to the logistical challenges faced by Non-Governmental Organizations (NGOs). The system connects donors, such as supermarkets and street market vendors, to recipients, such as NGOs, allowing the former to register products for donation and the latter to reserve them in an organized manner. The project was carried out following software engineering practices, including requirements gathering, modeling with use case and entity-relationship diagrams, and was implemented with modern technologies such as TypeScript, Node.js, and Prisma on the back-end, and React with Vite and Tailwind CSS on the front-end. The result is a functional web application that demonstrates the feasibility of utilizing technology to promote social responsibility and streamline the donation process.